2014
DOI: 10.1016/j.chemosphere.2014.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated dibenzo-p-dioxins and dibenzofurans in water and six fish species from Dongting Lake, China

Abstract: h i g h l i g h t sThe PCDD/Fs concentrations in eight water samples from Dongting Lake were determined. PCDD/Fs concentrations were above that allowed by the US EPA. 2,3,7,8-Chlorinated PCDD/F concentration differed in six fish species. The bioaccumulation of PCDD/F congeners cannot solely be explained by their physical-chemical properties. a r t i c l e i n f o a b s t r a c tThere have been few studies of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) in environmental water because of the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…In the atmosphere, PCDD/Fs and DL-PCBs may be transported into the ocean and rivers via environmental deposition and may affect the health of aquatic animals. The PCDD/Fs and DL-PCBs are widely distributed in the aquatic environment and accumulate in aquatic organisms, being integrated into the food chain [ 12 ]. Hyo-bang Moon et al [ 13 ] recorded the highest levels of PCDD/Fs and DL-PCBs residues in crustaceans followed by fish.…”
Section: Introductionmentioning
confidence: 99%
“…In the atmosphere, PCDD/Fs and DL-PCBs may be transported into the ocean and rivers via environmental deposition and may affect the health of aquatic animals. The PCDD/Fs and DL-PCBs are widely distributed in the aquatic environment and accumulate in aquatic organisms, being integrated into the food chain [ 12 ]. Hyo-bang Moon et al [ 13 ] recorded the highest levels of PCDD/Fs and DL-PCBs residues in crustaceans followed by fish.…”
Section: Introductionmentioning
confidence: 99%
“…To capture dissolved dioxins, Gao et al (2014) [37] suggested filtering the water samples and running them through a column made of the hydrophobic resin XAD-2. Following drying, the dioxins are eluted using a 1:1 mixture of dichloromethane and hexadecane.…”
Section: The Most Common Methods For Analysis and Detectionmentioning
confidence: 99%
“…然而, 我国关于 五氯酚及其钠盐污染区域膳食中PCDD/Fs污染水平 的研究较少. Fang等人 [40] 研究表明, 洞庭湖地区鸟蛋 中 PCDD/Fs含量低于鸟蛋中PCDD/Fs的毒性阈值标 准. Gao等人 [41] [7,42,43] . 2011年 [44] .…”
Section: 纪50年代中期 我国长江流域南部多省血吸虫病流 行 五氯酚及其钠盐被广泛用来杀灭血吸虫的宿主unclassified